2021
DOI: 10.1038/s41433-020-01379-9
|View full text |Cite
|
Sign up to set email alerts
|

Dupilumab-associated ocular surface disease: presentation, management and long-term sequelae

Abstract: Objectives To determine the presenting features of ocular surface disease in patients with atopic dermatitis (AD) treated with dupilumab at a tertiary, university hospital. To establish the need for treatment of dupilumab-associated ocular surface disease and report any long-term effects on the ocular surface. Methods A retrospective analysis of consecutive patients treated with dupilumab for AD between January 2017 and August 2019 was undertaken. Data wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 29 publications
3
78
0
Order By: Relevance
“…In most patients suffering from dupilumab-associated conjunctivitis, the severity is mild to moderate ( Achten et al., 2021 ; Nahum et al., 2020 ; Nettis et al., 2020a ; Touhouche et al., 2021 ), but severe cases or those with persistent conjunctivitis have been reported ( Barnes et al., 2017 ; Li et al., 2020 ; Paulose et al., 2019 ; Popiela et al, 2021 ; Vingopoulos and Lazzaro, 2020 ). Dose adjustment or discontinuation of dupilumab is needed in certain cases ( Achten et al., 2021 ).…”
Section: Specific Concerns With Dupilumab Treatment In Patients With Admentioning
confidence: 99%
See 1 more Smart Citation
“…In most patients suffering from dupilumab-associated conjunctivitis, the severity is mild to moderate ( Achten et al., 2021 ; Nahum et al., 2020 ; Nettis et al., 2020a ; Touhouche et al., 2021 ), but severe cases or those with persistent conjunctivitis have been reported ( Barnes et al., 2017 ; Li et al., 2020 ; Paulose et al., 2019 ; Popiela et al, 2021 ; Vingopoulos and Lazzaro, 2020 ). Dose adjustment or discontinuation of dupilumab is needed in certain cases ( Achten et al., 2021 ).…”
Section: Specific Concerns With Dupilumab Treatment In Patients With Admentioning
confidence: 99%
“…Keratitis ( Akinlade et al., 2019 ) is also reported. The timing of the onset of conjunctivitis after initiating dupilumab in patients with AD differed from 2 weeks to 4 months in individual reports ( Nahum et al., 2020 ; Nettis et al., 2020a ; Popiela et al, 2021 ; Uchida et al., 2020 ).…”
Section: Specific Concerns With Dupilumab Treatment In Patients With Admentioning
confidence: 99%
“…Although this is a relatively new therapy in severe asthma, there are longer-term safety data available following its use in the treatment of atopic dermatitis. In patients with atopic dermatitis treated with dupilumab, a high incidence of conjunctivitis has been reported [ 86 ].…”
Section: Dupilumabmentioning
confidence: 99%
“…A recent meta-analysis has confirmed that conjunctivitis is the most common adverse event, reported in 26.1% of patients [ 87 ]. The pathogenesis of these side effects is at present unknown [ 88 , 89 , 90 ]. In children, the treatment was well tolerated in the long term and the most frequent adverse reaction was nasopharyngitis [ 91 ].…”
Section: Therapeutic Approach To Atopic Dermatitismentioning
confidence: 99%